2018
DOI: 10.3390/ijms19061633
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Mechanical Properties of a DNA Hydrogel in Three Phases Based on ATP Aptamer

Abstract: By integrating ATP aptamer into the linker DNA, a novel DNA hydrogel was designed, with mechanical properties that could be tuned into three phases. Based on the unique interaction between ATP and its aptamer, the mechanical strength of the hydrogel increased from 204 Pa to 380 Pa after adding ATP. Furthermore, with the addition of the complementary sequence to the ATP aptamer, the mechanical strength could be increased to 570 Pa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…For instance, Liu et al used ATP binding aptamers to control the mechanical strength of their DNA hydrogels. They showed that in the presence of ATP their hydrogels exhibit a G' of 380 Pa and a G' of 204 Pa in the absence of ATP [33]. Moreover, they demonstrated the ATP concentration dependence of their system that allows for fine-tuning of the hydrogel's mechanical properties.…”
Section: Nucleic Acid Structural Motifsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Liu et al used ATP binding aptamers to control the mechanical strength of their DNA hydrogels. They showed that in the presence of ATP their hydrogels exhibit a G' of 380 Pa and a G' of 204 Pa in the absence of ATP [33]. Moreover, they demonstrated the ATP concentration dependence of their system that allows for fine-tuning of the hydrogel's mechanical properties.…”
Section: Nucleic Acid Structural Motifsmentioning
confidence: 99%
“…While DNA building blocks have been used extensively to assemble several nanoscale objects, DNA as a material is now gaining more traction as a potential candidate for larger scale polymeric biomaterials assembly, particularly to build nanostructured functional soft hydrogels with sizes ranging from the nanoscale to the millimeter scale. Similar to the discrete DNA nanostructures, the structural, mechanical, and biochemical properties of these DNA hydrogels are highly controllable [31][32][33]. In the past decade, several studies have demonstrated the potential of these DNA hydrogels to be used in several biomedical applications [34] including drug delivery [35][36][37], cancer therapy [38][39][40], antigen delivery and immunomodulation [41,42], sensing [43][44][45], and extracellular matrix (ECM) mimics for tissue engineering [34,46].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond self-assembly, DNA is also biocompatible and can be readily conjugated with other bio-/nanomaterials including proteins and conductive polymers [6][7][8][9]. Leveraging these capabilities, DNA-based hydrogels have drawn a lot of attention starting with basic research and moving to applications such as biomedicine, biosensing, and drug delivery [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, stimuli‐responsive DNA hydrogels have also been designed and prepared by taking advantage of the predictable hybridization of DNAs, along with unique DNA sequences (i‐motif, G‐quadruplex, and triplex), functionalized DNAs, or aptamers. They exhibited a phase transition from the gel state to sol state in response to various stimuli such as heat, pH, light, metal ions, and biomolecules (nucleic acids, proteins, enzymes, and small molecules) . In particular, biological stimuli‐responsive DNA hydrogels have successfully been applied for drug‐delivery systems, cell engineering, and biosensing systems .…”
Section: Introductionmentioning
confidence: 99%